The Effect of Female Directors on ESG Practice: Evidence from China - Hongyu Peng; Tirapot Chandarasupsang (International Journal of Financial Studies, 2023)
This paper empirically examines the impact of female directors on corporate ESG disclosure scores based on upper echelons theory and women’s ethics of care theory by conducting a multiple regression analysis on 8193 observations of Chinese listed companies from 2010 to 2020. Our results demonstrate the importance of female directors’ participation in promoting corporate ESG practices. We conclude that the higher the proportion of female directors on the board, the higher the corporate ESG practice score. Further analysis also revealed that a favorable institutional environment and non-state enterprises positively moderate the relationship between female directors and corporate ESG practices. These results highlight the significant contribution of female directors to corporate ESG practices. Our paper sheds additional light on issues related to female directors and corporate ESG practices in Chinese listed companies, expands the theoretical knowledge of ethical decision-making and institutional environments in listed companies, enriches research in the area of female directors’ decision-making, and has important implications for corporate governance related policy-making in China.